A local two-way partnership for teacher development. (May 2023) - Scheurman, Geoffrey; Yell, Michael
Middle school teacher Michael Yell and education professor Geoffrey Scheurman discuss a decades-long partnership of ongoing professional development opportunities that involve teachers, university faculty, and teacher candidates working together to create personalized, meaningful, and sustained initiatives that enhance the growth and skills of all those involved. The resulting professional laboratory includes classroom collaborations, preservice teachers shadowing students, school/university exchanges, and the ability to take advantage of learning opportunities that arise organically. The results are reciprocal, inexpensive, ongoing, administrator-approved, and self-directed professional development experiences any teacher-professor duo can consider as they build their own laboratory.